Thermal behavior of grain-oriented electrical steel wound core solid-state transformer. Issue 2 (14th February 2022) - Ichou, Houssam; Roger, Daniel; Rossi, Mathieu
Abstract : Purpose: This paper aims to propose a new design for high-power compact solid-state transformers (SSTs) made with grain-oriented electrical steel (GOES) wound cores that benefit from the natural reduction of iron losses at high temperatures. Design/methodology/approach: An experimental approach, coupled with numerical and analytical investigations, is widely used for proving the validity of the proposed concept. Findings: With cores much hotter than coils, the new design of medium frequency transformers can be used for building compact SSTs that rated powers and common-mode insulation voltages much higher than existing ones with similar efficiencies. Research limitations/implications: The thermal design must provide a large difference between core and coil temperatures in a reasonable volume. Practical implications: The increasing number of intermittent renewable sources place electric grid stability at risk. Smart nodes, made of SSTs, improve the global grid stability because they are able to provide real-time control of energy fluxes at critical points. In railway applications, high-power SST cells can be distributed along the train providing a larger volume for passengers. Social implications: The increasing part of electricity in a flexible grid requires performant and high-power SSTs made with components that have an environmental footprint as low as possible. Originality/value: This paper proves that the design of high-power transformers with GOES wound cores much hotter than coils is possible. It proposes also a thermal equivalent circuit that helps the design.